Kinematical signatures of hidden stellar discs - Magorrian, J (1999)
The deprojection of the surface brightness distribution of an axisymmetric galaxy does not have a unique solution unless the galaxy is viewed precisely edge-on. I present an algorithm that finds the full range of smooth axisymmetric density distributions consistent with a given surface brightness distribution and inclination angle, and use it to investigate the effects of this non-uniqueness on the line-of-sight velocity profiles (VPs) of two-integral models of both real and toy discy galaxies viewed at a range of inclination angles. Photometrically invisible face-on discs leave very clear signatures in the minor-axis VPs of the models (Gauss-Hermite coefficients h4 ≳ 0.1), provided the disc-to-bulge ratio is greater than about 3 per cent. I discuss the implications of these hitherto neglected discs for dynamical modelling.